2017
DOI: 10.7860/jcdr/2017/28603.10063
|View full text |Cite
|
Sign up to set email alerts
|

Kimura’s Disease without Peripheral Eosinophilia: An Unusual and Challenging Case Simulating Venous Malformation on Imaging Studies-Case Report and Review of literature

Abstract: Kimura's Disease (KD) is a rare chronic inflammatory disorder presenting as multiple painless solitary subcutaneous nodules, predominantly in the head and neck region and frequently associated with regional lymphadenopathy and/or salivary gland involvement. Because of painless nature and indolent course, there is usually a delay in the patient's presentation. KD may radiologically mimic other chronic inflammatory conditions like tuberculosis, vascular malformations and neoplasms. Clinical correlation and histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…The youngest patient was a 15-month old African American boy [ 7 ]. Although it is recognized that two typical laboratory examinations are elevated peripheral eosinophil and serum IgE, Vivek et al reported a case of KD without peripheral eosinophilia [ 4 ]. KD is characterized by subcutaneous masses in the head and neck region, sometimes with local lymph node enlargement and salivary gland involvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The youngest patient was a 15-month old African American boy [ 7 ]. Although it is recognized that two typical laboratory examinations are elevated peripheral eosinophil and serum IgE, Vivek et al reported a case of KD without peripheral eosinophilia [ 4 ]. KD is characterized by subcutaneous masses in the head and neck region, sometimes with local lymph node enlargement and salivary gland involvement.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of KD mainly depends on pathological examination. Treatment should aim to relieve symptoms and preserve aesthetics while preventing recurrences and long-term sequela [ 3 , 4 ]. In this study, we report a case of KD with ABPA in a Chinese man with special clinical manifestations.…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of KD mainly depends on pathological examination. Treatment should aim to relieve symptoms and preserve aesthetics while preventing the recurrences and long-term sequels [3,4]. In this study, we report a case of KD with ABPA in a Chinese man with special clinical manifestations.…”
mentioning
confidence: 89%
“…Macroscopically and radiologically, the tumour looks similar to inflammatory lesion typical for Kimura disease that has to be differentiated on histological level. Moreover, the disease is endemic and found mostly among man in the Far East [25]. Soft tissue haemangiomas, presently known as slow-flow venous malformations, are lesions with a high female predilection, commonly seen in all age groups, especially in children.…”
Section: Primary and Secondary Tumoursmentioning
confidence: 99%